'If i cannot have it, i will do everything i can to destroy it.' the canonization of Elliot Rodger: 'Incel' masculinities, secular sainthood, and justifications of ideological violence. (2nd September 2020) - Witt, Taisto
ABSTRACT: On May 23rd, 2014 in Isla Vista California, 22 year-old Elliot Rodger went on a killing spree that left 6 dead (including Rodger), and 14 wounded. Rodger was the first of as many as 6 North American mass killers who have been connected to an online community known as the Involuntary Celibate (or 'incel) community. This online space is populated by men who come together around a shared inability to find sexual or romantic partners. Online incel spaces have been observed referring to Rodger as 'Saint Elliot', or 'The Supreme Gentleman', and have been seen celebrating the anniversary of the Isla Vista killings as 'Saint Elliot Day'. Through an exploration of the affective and semiotic construction of 'Saint Elliot', and the treatment of Rodgers manifesto as a potentially hagiographic text, one can reveal ongoing projects of reality construction that allows for the justification, enactment, and celebration of extreme violence. These are projects which are intimately tied to the constructions of, and claims to, the masculinities of the men who make up this community.